An Olefin‐Linked Covalent Organic Framework as a Flexible Thin‐Film Electrode for a High‐Performance Micro‐Supercapacitor. (24th July 2019) - Xu, Junsong; He, Yafei; Bi, Shuai; Wang, Mao; Yang, Peng; Wu, Dongqing; Wang, Jianjian; Zhang, Fan
Abstract: Developing effective synthetic strategies as well as enriching functionalities for sp 2 ‐carbon‐linked covalent organic frameworks (COFs) still remains a challenge. Now, taking advantage of a variant of Knoevenagel condensation, a new fully conjugated COF (g‐C34 N6 ‐COF ) linked by unsubstituted C=C bonds was synthesized. Integrating 3, 5‐dicyano‐2, 4, 6‐trimethylpyridine and 1, 3, 5‐triazine units into the molecular framework leads to the enhanced π‐electron communication and electrochemical activity. This COF shows uniform nanofibrous morphology. By assembling it with carbon nanotubes, a flexible thin‐film electrode for a micro‐supercapacitor (MSC) can be easily obtained. The resultant COF‐based MSC shows an areal capacitance of up to 15.2 mF cm −2, a high energy density of up to 7.3 mWh cm −3, and remarkable rate capability. These values are among the highest for state‐of‐the‐art MSCs. Moreover, this device exhibits excellent flexibility and integration capability. Abstract : Ein vollständig konjugiertes kovalentes organisches Gerüst (COF) mit unsubstituierten C=C‐Linkern wurde mithilfe einer Variante der Knoevenagel‐Kondensation synthetisiert. Das COF wurde zu einer Dünnfilmelektrode für einen Mikro‐Superkondensator (MSC) verarbeitet. Dieser zeigte exzellente Kapazitäten von bis zu 15.2 mF cm −2, hohe Energiedichten von bis zu 7.3 mWh cm −3, bemerkenswerte Entladungsraten und herausragende Flexibilität.